2019
DOI: 10.1021/acs.biochem.9b00046
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Guided Adenosine Deaminases: Advances and Challenges for Therapeutic RNA Editing

Abstract: Targeted transcriptome engineering, in contrast to genome engineering, offers a complementary and potentially tunable and reversible strategy for cellular engineering. In this regard, adenosine to inosine (A-to-I) RNA base editing was recently engineered to make programmable base conversions on target RNAs. Similar to the DNA base editing technology, A-to-I RNA editing may offer an attractive alternative in a therapeutic setting, especially for the correction of point mutations. This Perspective introduces fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 107 publications
0
17
0
Order By: Relevance
“…Different SDRE promising platforms have been reported in recent literature [14][15][16][17]. Some are based on recruitment of native adenosine deaminases acting on RNA (ADARs) by antisense oligonucleotides (ASOs) [18][19][20], others on the recruitment of exogenous recombinant ADARs via the fusion to an RNA guide recognizing domain.…”
Section: Introductionmentioning
confidence: 99%
“…Different SDRE promising platforms have been reported in recent literature [14][15][16][17]. Some are based on recruitment of native adenosine deaminases acting on RNA (ADARs) by antisense oligonucleotides (ASOs) [18][19][20], others on the recruitment of exogenous recombinant ADARs via the fusion to an RNA guide recognizing domain.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the location of the target whether it should be in the 5′ (as we have done) or middle or 3′ position of the guideRNA, we have tried with different positions and we have found that the best efficiency we have got from the 5′ position (7th position in 21 bp guideRNA) of the target in the guideRNA (Supplementary datda 5 ). Katrekar et al (2019) also applied the guideRNA of 20 bp length and they placed the mismatch (at the site of target) at 6th position in 20 bp guideRNA 20 , 46 .…”
Section: Methodsmentioning
confidence: 99%
“…Several systems were recently developed to recruit ADAR enzymes to specific sites for site-directed RNA editing [23][24][25][26][27][28][29] , providing novel tools to study biological function and a safer and reversible alternative to gene therapy 23,[47][48][49] . These RNA engineering approaches use antisense RNA oligoribonucleotides as guide RNAs (gRNAs) to recruit either engineered or endogenous ADAR enzymes.…”
Section: Discussionmentioning
confidence: 99%